A Foresight Study on Smart Healthcare in Hospitals in Klang, Selangor - Alina Shamsuddin,; Kesavamoorthy, Pathmashalini; Wan Ahmad, Wan Nurul Karimah (Research in Management of Technology and Business, 2021)
Smart healthcare is when the patients are treated with digital medical equipments filled with Internet of Medical Things (IoMT). Recently, worsening trends like slowing rates of improvement can be linked to significant gaps in screening and treatment for NCDs (non-communicable diseases) such as hypertension and diabetes mellitus and the rising rates of key risk factors that can be expected to lead to future increases in NCDs in Malaysia. The research objectives are to identify the influencing factors and the impact and uncertainty by implementing smart healthcare in hospitals in Klang, Selangor for the next 10-15 years. Quantitative method and STEEPV analysis are used to conduct the study. Result shows that technology has the highest number of key drivers. Questionnaires and statistical analysis were used to identify the two top drivers which are quality of health services and government’s responsibility.